Aza-Diels-Alder Reactions with Lanthanide Triflates: Syntheses of Quinoline and Phenanthridine Derivatives - Turhan, Kadir; Pelit, Emel; Turgut, Zuhal (TAYLOR & FRANCIS INC, 2009)
The aza-Diels-Alder reactions of cyclopentadiene and cyclo-1,3-hexadiene with various substituted N-arylimines in the presence of Yb/Sc triflates as catalyst in MeCN at room temperature gave quinoline and phenanthridine derivatives in moderate to high yields. Some of the cycloaddition reactions were carried out in ionic liquid.
Keywords: Aza-Diels-Alder; heterocyclic compounds; phenanthridine; quinoline; triflates; N-ARYL IMINES; IONIC LIQUIDS; CYCLIZATION; Chemistry